A Panel Data Analysis of Foreign Trade Determinants of Nepal: Gravity Model Approach - Acharya, Subash (NRB Economic Review, 2013)
This study aims to identify the trade (export, import and trade balance) determinants of Nepal using extended gravity model and recommend specific trade policy to promote foreign trade. The gravity model of international trade takes notion from Newtonian physical science that the gravitational force between any two objects is proportional to the product of their masses and inversely proportional to distance; similarly, the trade between any two countries is proportional to the product of their GDPs and inversely proportional to distance. Empirical results based on panel data set containing 21 major trade partner countries for 6 years found that export and import of Nepal is explained by real GDP of trade partner countries. Increase in real GDP of trade partner countries increases both export and import; however, export increases at higher rate than import. The trade deficit of Nepal increases if real GDP of trade partner country increases, even though export is increasing at higher rate than import. This is because Nepal is importing more than exporting to those countries in absolute terms. Nepal exports more to SAFTA countries than non-SAFTA and imports less from the OECD countries than non-OECD. As per basic idea of gravity model, distance to trade partner countries is highly significant implying higher the distance, lower the trade. The country specific fixed effect analysis shows that time invariant factors are also significant to determine the trade balance of Nepal.